Management of Prader-Willi Syndrome - Butler, Merlin G.; Lee, Phillip D. K.; Whitman, Barbara Y.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Now in a fully revised and updated fourth edition, this book remains the most comprehensive resource on Prader-Willi syndrome (PWS) available on the market. There have been significant changes in the diagnosis, clinical care and treatment of PWS since the previous edition was published in 2006, and more thorough information on understanding the cause and diagnosis of the condition, along with clinical presentation and findings with natural history data now available. The book is divided into three thematic sections. Part One discusses the genetics, diagnosis, research and overview of PWS, including current laboratory testing. The medical physiology and treatment of PWS comprise Part Two, covering the GI system, obesity as well as the use of growth hormone. Part Three, the largest section, presents a wide-ranging, multidisciplinary management approach to PWS, attending to the many manifestations of the condition. Topics here include neurodevelopmental aspects, speech and language disorders, motor issues, psychological and behavioral management, educational and transitional considerations, vocational training and residential care, and advocacy for both school discipline and sexuality. Syndrome-specific growth charts, benefits eligibility information and additional resources are included in helpful appendices. Timely and well-crafted, this latest edition of Management of Prader-Willi Syndrome remains the gold standard for clinicians and health care providers working with patients diagnosed with this rare obesity-related genetic disorder.
Part I: Diagnosis and Genetics of Prader-Willi Syndrome -- Clinical Findings and Natural History of Prader-Willi Syndrome -- Diagnostic Criteria for Prader-Willi Syndrome -- Molecular Genetic Findings in Prader-Willi Syndrome -- Laboratory Testing for Prader-Willi Syndrome -- Part II: Medical Physiology and Treatment of Prader-Willi Syndrome -- Medical Considerations in Prader-Willi Syndrome -- Gastrointestinal System, Obesity, and Body Composition -- Growth Hormone and Prader-Willi Syndrome -- Part III: Multidisciplinary Management of Prader-Willi Syndrome -- Neurodevelopmental and Neuropsychological Aspects of Prader-Willi Syndrome -- Speech and Language Disorders Associated with Prader-Willi Syndrome -- Motor and Developmental Interventions for Prader-Willi Syndrome -- Educational Considerations for Children with Prader-Willi Syndrome -- Tools for Psychological and Behavioral Management with Prader-Willi Syndrome -- Educational and Social Issues for Adolescents with Prader-Willi Syndrome -- Transition from Adolescence to Young Adulthood: The Special Case of Prader-Willi Syndrome -- Vocational Training for People with Prader-Willi Syndrome -- Residential Care for Adults with Prader-Willi Syndrome -- Inpatient Crisis Intervention for Persons with Prader-Willi Syndrome -- Social Work Interventions: Advocacy and Support for Families with Prader-Willi Syndrome -- A National Approach to Crisis Intervention and Advocacy with Prader-Willi Syndrome -- Advocacy Issues with Prader-Willi Syndrome: School Discipline and Expulsion -- Advocacy Issues with Prader-Willi Syndrome: Sexuality.
Keywords: Endocrinology; Pediatrics; Psychiatry; Endocrinology; Pediatrics; Psychiatry; Prader-Willi Syndrome